The impact of thin capitalization rule on tax avoidance in Indonesia - Muhammad Rheza Ramadhan (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: This study aims to investigate the impact of the thin capitalization rule on tax avoidance in Indonesia.Design/Methodology/Approach: The analysis used event study regression to overcome the problem of committed variable bias. Research findings: The examination found that, over the entire period, the thin capitalization rule could reduce tax avoidance. However, this study also uncovered that even though tax avoidance was reduced, the company did not pay the tax in the current year but postponed it to the following years. In addition, this study revealed that the thin capitalization rule could only reduce tax avoidance for a sub-sample of non-manufacturing companies. As for manufacturing companies, the thin capitalization rule had no impact on tax avoidance.Theoretical contribution/Originality: This research is the first to examine the impact of the thin capitalization rule on tax avoidance using a suitable method, i.e., event study regression with a staggered setup.Practitioner/Policy implication: This study can show that the thin capitalization rule works well for non-manufacturing companies. However, for manufacturing companies, the Indonesian tax authorities need to consider other ways to reduce their tax avoidance, for example, by creating or updating other specific anti-tax avoidance rules, such as transfer pricing or treaty shopping.